Indirect reciprocity, golden opportunities for defection, and inclusive reputation - Max Albert; Hannes Rusch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
In evolutionary models of indirect reciprocity, reputation mechanisms can stabilize cooperation even in severe cooperation problems like the prisoners dilemma. Under certain circumstances, conditionally cooperative strategies (cooperate iff your partner has a good reputation) cannot be invaded by any other strategy that conditions behavior only on own and partner reputation. Still, the evolutionary version of backward induction can lead to a breakdown of this kind of indirect reciprocity. Backward induction, however, requires strategies that count and then cease to cooperate in the last, last but one, last but two, game they play. These strategies are unlikely to exist in natural settings. We present two new findings. (1) Surprisingly, the same kind of breakdown is also possible without counting. Opportunists using rare golden opportunities for defection can invade conditional cooperators. This can create further golden opportunities, inviting the next wave of opportunists, and so on, until cooperation breaks down completely. (2) Cooperation can be stabilized against these opportunists by letting an individuals initial reputation be inherited from that individuals parent. This inclusive reputation mechanism can cope with any observably opportunistic strategy. Offspring of opportunists who successfully exploited a conditional cooperator cannot repeat their parents success because they inherit a bad reputation, which forewarns conditional cooperators in later generations.
Keywords: C73; D03; D64; 330; evolutionary game theory; repeated prisoner's dilemma; backward induction; conditional cooperation; opportunism